Conformational isomerism of pyrimidine nucleosides isolated in the low temperature inert matrices - A.Yu. Ivanov, A.Yu. (Biophysical Bulletin, 2002)
For the first time, conformational structures of 2-deoxyuridine (dU) and thymidine (T) were investigated by using Fourier transform infrared (FTIR) matrix isolation spectroscopy. The FTIR spectra of dU and T in Ar matrices were obtained in the range 4000-1400 cm-1-1. The stability of conformers was estimated by the methods HF/3-21G (p), HF/6-31G (d, p), and MP2/6-31G (d, p). Ab initio calculations of the infrared spectra were performed by the methods HF/3-21G(p), HF/6-31G (d, p). The actual occupancy of conformational isomers in matrix samples was determined. It was shown that anti conformers of dU and T are dominant. The ribose rings of main anti conformers al1, a00 are in the С2’’-endo conformation, but the ribose rings of low-occupying anti-conformers a22, a33 have the СЗ’-exo conformation, stabilized by intramolecular hydrogen bonds ОЗ’Н—05’ and 05’Н—03’ accordingly. Syn conformers of these nucleosides are stabilized by the intramolecular hydrogen bond 05’Н—02, and the dominant conformation of the ribose ring is С2’-endo.